EDUCATIONAL VALUES FOR STUDENT CHARACTER BUILDING (A HERMENEUTIC ANALYSIS) - Desyandri Desyandri (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2016)
This article aims to discover, interpret, and identify the educational values embodied in the song of Minangkabau creation by NN. The identification process is done by a multidisciplinary hermeneutic analysis. Interpretation is generated by associating the aspects of language, music/songs, psychological, socio-cultural, and educational, so it can be identified seven (7) educational values. The educational values is a means to educate learners to perform the actions and behaviors that reflect proper Minang people. Education and learning as a means of cultural inheritance are obliged to explore, socialize, actualize, and cultivate the educational values on an ongoing basis in order to create learners who are well-mannered, civilized and noble character